Effect of Nanoparticle Weight on the Cellular Uptake and Drug Delivery Potential of PLGA Nanoparticles - Kattel, Prabhat; Sulthana, Shoukath; Trousil, Jiří; Shrestha, Dinesh; Pearson, David; Aryal, Santosh (ACS omega, 2023)
Biodegradable and biocompatible polymeric nanoparticles (NPs) stand out as a key tool for improving drug bioavailability, reducing the inherent toxicity, and targeting the intended site. Most importantly, the ease of polymer synthesis and its derivatization to add functional properties makes them potentially ideal to fulfill the requirements for intended therapeutic applications. Among many polymers, US FDA-approved poly(l-lactic-co-glycolic) acid (PLGA) is a widely used biocompatible and biodegradable co-polymer in drug delivery and in implantable biomaterials. While many studies have been conducted using PLGA NPs as a drug delivery system, less attention has been given to understanding the effect of NP weight on cellular behaviors such as uptake. Here we discuss the synthesis of PLGA NPs with varying NP weights and their colloidal and biological properties. Following nanoprecipitation, we have synthesized PLGA NP sizes ranging from 60 to 100 nm by varying the initial PLGA feed in the system. These NPs were found to be stable for a prolonged period in colloidal conditions. We further studied cellular uptake and found that these NPs are cytocompatible; however, they are differentially uptaken by cancer and immune cells, which are greatly influenced by NPs' weight. The drug delivery potential of these nanoparticles (NPs) was assessed using doxorubicin (DOX) as a model drug, loaded into the NP core at a concentration of 7.0 ± 0.5 wt % to study its therapeutic effects. The results showed that both concentration and treatment time are crucial factors for exhibiting therapeutic effects, as observed with DOX-NPs exhibiting a higher potency at lower concentrations. The observations revealed that DOX-NPs exhibited a higher cellular uptake of DOX compared to the free-DOX treatment group. This will allow us to reduce the recommended dose to achieve the desired effect, which otherwise required a large dose when treated with free DOX. Considering the significance of PLGA-based nanoparticle drug delivery systems, we anticipate that this study will contribute to the establishment of design considerations and guidelines for the therapeutic applications of nanoparticles.